PHYTOCHROME INTERACTING FACTOR 7 is important for early responses to elevated temperature in Arabidopsis seedlings. Issue 1 (29th November 2019) - Fiorucci, Anne-Sophie; Galvão, Vinicius Costa; Ince, Yetkin Çaka; Boccaccini, Alessandra; Goyal, Anupama; Allenbach Petrolati, Laure; Trevisan, Martine; Fankhauser, Christian
Summary: In response to elevated ambient temperature Arabidopsis thaliana seedlings display a thermomorphogenic response that includes elongation of hypocotyls and petioles. Phytochrome B and cryptochrome 1 are two photoreceptors also playing a role in thermomorphogenesis. Downstream of both environmental sensors PHYTOCHROME INTERACTING FACTOR 4 (PIF4) is essential to trigger this response at least in part through the production of the growth promoting hormone auxin. Using a genetic approach, we identified PHYTOCHROME INTERACTING FACTOR 7 (PIF7) as a novel player for thermomorphogenesis and compared the phenotypes of pif7 and pif4 mutants. We investigated the role of PIF7 during temperature‐regulated gene expression and the regulation of PIF7 transcript and protein by temperature. Furthermore, pif7 and pif4 loss‐of‐function mutants were similarly unresponsive to increased temperature. This included hypocotyl elongation and induction of genes encoding auxin biosynthetic or signalling proteins. PIF7 bound to the promoters of auxin biosynthesis and signalling genes. In response to temperature elevation PIF7 transcripts decreased while PIF7 protein levels increased rapidly. Our results reveal the importance of PIF7 for thermomorphogenesis and indicate that PIF7 and PIF4 likely depend on each other possibly by forming heterodimers. Elevated temperature rapidly enhances PIF7 protein accumulation, which may contribute to the thermomorphogenic response.